Factors Responsible for Displacement and Its Impact (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The study's findings indicate that relocation is a complex phenomenon resulting from a combination of events, including warfare, environmental disturbances, and economic difficulties. The repercussions of this have far-reaching implications for society, impacting both people and organisations, as well as the civilizations they were previously part of. From an economic standpoint, displacement causes a disruption in people' means of making a living, resulting in unemployment, poverty, and placing a burden on the resources of the communities that provide shelter. From a social perspective, it causes the fragmentation of community cohesion, leaving displaced persons vulnerable to prejudice and difficulties in adjusting to their new environment. Psychologically, displacement is characterised by feelings of stress, anxiety, and a sense of deprivation, particularly when one is separated from cultural and social ties. This may have negative effects on education and health. To effectively intervene, it is necessary to implement policies that tackle economic regeneration, social integration, and comprehensive mental health aid, considering the wide-ranging consequences of these actions. To mitigate the adversities caused by displacement and promote resilient, inclusive communities, society must comprehend the complex relationships that contribute to displacement and recognise its multiple impacts. The objective of this research is to thoroughly understand the complexities of displacement and shed light on its consequences, providing a basis for well-informed and compassionate approaches to tackle this worldwide situation.